Funcionalidad familiar y estilo de vida en usuarios de la estrategia sanitaria escolar y adolescente. Guadalupe - 2016 - Campos Correa, Katterin Noelia (2016)
The purpose of this quantitative study descriptive, was to test the relationship between family functioning and lifestyle of adolescents. Research subjects were adolescents of both sexes, users of school and adolescent health strategy Tomas Hospital Lafora, who live in the town of Guadalupe, Pacasmayo province, La Libertad department; in the period from January 2016. Using SPSS version 20 for Windows and statistical test “Chi - square" (X2). Concluding that 60.7 percent of adolescents are familiar functionality of a functional type and 39.3 percent showing family dysfunction. 63.3 percent of adolescents have a healthy lifestyle, while 36.7 percent has an unhealthy lifestyle. At the same time it was shown that there is significant relationship between family functioning and lifestyle of users in study (p value < 0.05). That makes infer that the more familiar functionality of functional type, have greater chances of finding healthy lifestyle.